The Role Of Startups In The Age Of Covid-19 Pandemic - Evidence From The World - - Boulesnam, Mohamed; Seguiri, Sidali; Kebtan, Chaouki (جامعة الوادي - University of Eloued, 2021)
This study aims to provide startups' experience evaluation during crises and set startups’ mechanisms that could help in alleviating the effects of the current pandemic in different countries. Several experiences from the US, UK, Japan, and some Arab countries have been presented in this study to illustrate the role of startups in the age of this pandemic. The study concluded that startups have played major roles in the age of Covid19, particularly in the health sector. But, they should adopt the innovation mindset, and face challenges using technological changes and internet advantages
مقال
Keywords: Startups ; Age of Crisis ; Covid-19 Pandemic